2023
DOI: 10.3390/fire6030100
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and CFD Simulation of Regression Rate in Hybrid Rocket Motors

Abstract: As the research on hybrid rocket motors advances, more accurate tools are needed to estimate the performance of the system by determining its fundamental parameters. One of them is certainly the regression rate of the solid fuel. Unfortunately, it depends on many complex physical phenomena and interactions which vary with time, space and scale, making the task of predicting its evolution very difficult. To address this issue, Computational Fluid Dynamics (CFD) was employed to investigate the inner workings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Our maximum value for temperature and velocity are about 2700 o C and 160m/s, respectively, what gives the differences between obtained maximum values at the level of 20% for both parameters. In contrast, Rampazzo et al [2] under similar assumptions showed a maximum temperature of 3100 o C and a velocity of about 150m/s. In contrast to proposed model it gives the differences about 13% with respect to the predicted temperature and 7% according to calculated velocity.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Our maximum value for temperature and velocity are about 2700 o C and 160m/s, respectively, what gives the differences between obtained maximum values at the level of 20% for both parameters. In contrast, Rampazzo et al [2] under similar assumptions showed a maximum temperature of 3100 o C and a velocity of about 150m/s. In contrast to proposed model it gives the differences about 13% with respect to the predicted temperature and 7% according to calculated velocity.…”
mentioning
confidence: 84%
“…Conventional rocket fuels are liquid or solid fuels. Today, a growing body of work in the aviation literature is concerned with experimental and theoretical research into the possibility of improving the efficiency and reducing the cost of rocket flight by using hybrid systems in which the fuel and oxidizer are in two different phases (solid and liquid) [1][2][3][4][5]. The main criteria for the use of this type of rocket propulsion are the simplicity of the system itself and the associated lower cost and operational safety of the entire device.…”
Section: Introductionmentioning
confidence: 99%
“…Moving forward, the hybrid exhausts characteristics should be more carefully taken into account in the future. In any case, the non-premixed turbulent diffusive flame of hybrid rockets [111][112][113][114][115][116][117][118][119][120][121][122], burning a solid material, could probably never compete with the best liquid engines burning liquid methane, or even less with liquid hydrogen. Additionally, methane-fueled engines can be expected to emit, uniquely, potentially significant amounts of hydrogen oxides (HOx) into the stratosphere [93].…”
Section: Preliminary Assessmentmentioning
confidence: 99%